TEKNIK ITERASI VARIASIONAL UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Koko Saputra; Supriadi Putra; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the variational iteration technique to solve nonlinear equations. This iterative technique is obtained by estimating the second derivative that appears in the variational iteration method. Then by choosing certain functions in the form of exponents, three iterative methods of order three are found. Because the three methods require two evaluations of the function and one evaluation of the derivative function, then the eciency index of the three methods that have been suggested is 1:442, greater than the eciency index of Newton's method that is 1; 414.